A Note on $k$-Ideals in Ternary Semirings (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we give some examples of $k$-ideals of ternary semirings. We examine the results of $k$-ideals by distinguished classes in ternary semirings, which include $k$-maximal, $k$-prime and $k$-semiprime.
Keywords: ternary semirings; k-ideals; k-maximal; k-prime; k-semiprime